숙성이 제주마 등심의 육질과 관능적 특성에 미치는 영향 - 성필남; 이종언; 박범영; 하경희; 고문석 (Journal of animal science and technology, 2006)
The purpose of this study was to assess the influence of ageing time on the meat quality and sensory characteristics of longissimus muscle in Jeju horses. Twenty four horses were slaughtered after 16hr fasting. Longissimus muscle was separated from the left half of the carcass after 24hr chilling. The muscle was sliced into 3cm-thick steaks for analysis. Steaks were vacuum packaged and aged at around 4℃ for 1, 3, 7, 12, 18 and 25 days respectively. Longissimus muscle pH was not influenced by ageing (P>0.05). But shear force values of the muscle decreased during ageing time (P<0.05). Water holding capacity, color characteristics, cooking loss and purge loss considerably increased as the ageing time increased (P<0.05). Also ageing had a very important effect on flavor, juiciness, tenderness and palatability characteristics (P<0.05) evaluated by the panel. Flavor and palatability were the most acceptable when the ageing time was 7 days, whereas, juiciness was 12 days. These results suggest that ageing improves the quality of horsemeat by increasing the meat tenderness, water holding capacity and sensory characteristics. Therefore Jeju horse meat need 7-12 days ageing period to obtain an optimum acceptance. 연도증진의 가장 일반적인 방법인 숙성을 통해 말고기의 육질과 관능적 특성이 어떻게 변화하는지를 조사하여 말고기의 적정 숙성기간을 제시하고, 국내 말고기의 냉장 유통에 대비한 기초자료를 확보하고자 제주마 24두의 등심을 4℃에서 25일간 숙성시키면서 육질과 관능적 특성을 조사하였다. 말고기 pH는 숙성기간에 따라 차이가 없었으며, 전단력은 저장 12일까지 유의적으로 감소하다가(P<0.05) 12일 이후 차이를 나타내지 않았다. 보수력, 가열감량 및 포장감량은 숙성기간이 경과할수록 증가하는 경향이였으며, 육색특성은 숙성기간이 경과할수록 명도(L*)와 적색도(a*) 값이 증가하는 경향을 보였다. 관능적 특성 중 풍미는 저장 7일에 가장 높은 수치를 나타내었고, 다즙성은 숙성 12일에 패널에 의해 가장 좋은 점수를 받았으며, 연도는 숙성 7일에 유의적인 증가를 보였으며(P<0.05) 이후 숙성기간에는 차이가 없었다. 숙성기간별 말고기에 대한 전체기호도는 숙성 7일에 유의적인 증가를 보인 후 숙성 18일까지 지속하다가 25일에 다소 감소하였다(P<0.05). 이상의 결과로 볼 때 말고기 등심의 최적숙성기간은 도축 후 9～14일로 나타났으며, 도축 후 20일 이후에는 기호성과 육질이 저하되는 결과를 보였다.